Pancasila Dalam Interaksi Kearifan Lokal Dan Ideologi Transnasional - Bhagaskoro, Pradipto; Utungga Pasopati, Rommel; Syarifuddin, Syarifuddin (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2019)
Today, 'transnational ideology' is much assumed as a threat for Indonesian local wisdom. Then, how can local wisdom survive amid the spread of transnational ideology? In essence, current recognized Indonesian religions, even coming from outside Nusantara, are well received because of their interaction with local conditions. These religions open, understand, and accommodate local conditions in order to conform to their teachings. The key point of religious life in Indonesia is the spectrum of its understanding with local wisdom. This paper describes the interaction between local wisdom and transnational ideology in Indonesia and how Pancasila should function in this condition. The first part of this paper describes local wisdom as a cultural product and its habitual manifestations. Second, explanations of transnational ideology and its relations to religions in Indonesia. Third, Pancasila is a reflection of local Indonesian wisdom and a path of interaction with any party, including transnational ideologies that are not yet understood. Fourth, conclusion that explains Pancasila as a form of nation-state presence that provides further understanding for local wisdom towards transnational ideology. This condition may happen as long as the spirit of mutual understanding becomes the basis for every interaction that may come.